Health risk due to exposure to chlorpyrifos for farmers in Thai Binh: Probabilistic risk assessment - Phung Tri Dung; Hung Nguyen-Viet; Tran Thi Tuyet Hanh (2013)
Farmers in Vietnam are at high risk of exposure to pesticides, especially with chlorpyrifos, the most common insecticide registered for use in 2009 in Vietnam. The purpose of this study was to assess the health risks of chlorpyrifos exposure in farmers who were pesticide applicators. The research method included three steps: (i) 24-hour urine samples taken from farmers to analyse trichlorpyridinol (TCP), the main metabolite of chlorpyrifos, and then TCP was converted to Absorbed Daily Dose (ADD); (ii) dose-response (RADD) corresponding to acute effects on the nervous system was obtained and recalculated from epidemiologic studies on human population; (iii) the health risk of chlorpyrifos with farmers was evaluated using probabilistic health risk assessment approach with 10,000 trials simulated by Monte Carlo technique. The results showed that the baseline exposure level (ADDB) ranged from 0.03 - 1.98 µg/kg/d, and post-application exposure level (ADDA) ranged from 0.35 - 94 µg/kg/d. The total exposure level (ADDT), ranged from 0.4 - 94.2 µg/kg/d. Dose-response corresponding to neurological adverse effects (RADD) ranged from 5-181 µg/kg/d. The Hazard Quotient calculated from ADD and RADD revealed that the baseline exposure level did not contribute to a significant adverse effect, however the post-application and total exposure levels caused a high risk of adverse effects to farmers who were pesticide applicators at 33%. A needs assessment and intervention studies need to be conducted to explore methods to reduce the risks due to chlorpyrifos exposure among farmers.